Criminal Law Politics on The Granting of Reintegration Rights to Community Inmates (Study at Class II A Binjai Prison) - Sudarno Hariadi Nasution; Abdul Rahman Maulana Siregar; Ismaidar Ismaidar (CV. Era Digital Nusantara, 2025)
Indonesia's national legal policy is based on the state's vision, as formulated in the Preamble to the 1945 Constitution of the Republic of Indonesia, namely to protect the entire nation, advance public welfare, and enhance the nation's intellectual life, as well as to contribute to maintaining world order to achieve social justice.This research was conducted in Binjai City, specifically at the Class II A Binjai Penitentiary Office. This research employed an empirical juridical approach. Data obtained in the field were presented descriptively using an empirical normative approach.This research aimed to determine the criminal law policy regarding the granting of reintegration rights to inmates at the Class II A Binjai Penitentiary and the obstacles encountered in granting reintegration rights to inmates at the Class II A Binjai Penitentiary. Based on the research findings, the author found that the implementation of the rules and policies granting reintegration rights to inmates is based on Law No. 12 of 1995, which has been amended by Law No. 22 of 2022 concerning Corrections. The obstacles faced in granting reintegration rights come from the correctional inmates themselves due to a lack of concern for the administrative rules and conditions stipulated for granting reintegration rights to correctional inmates.